The importance of corporate identity in the higher education institutions (2016)
Corporate identity in management is a factor in the generation of competitive advantage in dynamic environments. This concept refers to a set of features that give specificity, stability and consistency to organizations. In this article, we review how the concept of corporate identity has been defined in different disciplines from a management perspective. Additionally, we proposed a new empirical application for the higher education institutions (IES by its acronym in Spanish) case.